Effect of concentration of sugar and dried Dayak onion (Eleutherine palmifolia) on the quality of Dayak onion kombucha - Permatasari, Vitta Rizky; Widayanti, Vindhya Tri; Falasifah, Ratu; Sunyoto, Nimas Mayang Sabrina; Suhartini, Sri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Kombucha is one example of a health drink product that falls under the category of functional drinks. Dayak onions are one of the ingredients with many bioactive components. This study aimed to determine the optimal combination of treatments to yield the highest quality Dayak onion kombucha by assessing the effects of variations in sugar concentration and dried Dayak onion concentration on the quality of Dayak onion kombucha (i.e., pH, total acid, and organoleptic). The study employed a randomized block design (RBD) with three replications to produce 27 experimental units. The two factors were dried Dayak onion concentrations of 2%, 4%, and 6% (w/v) and sugar concentrations of 5%, 7.5%, and 10% (w/v). The data was then subjected to a two-way ANOVA using IBM SPSS Statistics 26 software, and the Multiple Attribute method was used to determine the best treatment. The results demonstrated that the concentration of sugar and dried Dayak onions had a significant effect (α<0.05) on the pH value, total acid. the higher the concentration of sugar, the higher the total acid content with a lower pH, and the higher the concentration of dried Dayak onions, the lower the total pH. The best treatment combination was using dried Dayak onion concentration of 6% (w/v) and sugar concentration of 7.5% (w/v). The test results obtained were pH 3.173, total acid 0.105%, organoleptic color 3.867, and organoleptic aroma 2.867.